Intensive remedial program for pupils at risk of dysgraphia: A single case study - Choi Lean, Esther Kwe (Jurnal Pendidikan Bitara UPSI, 2019)
This study employed a single case about implementing a remedial program to help pupil at-risk of dysgraphia in order to hold a pencil with the correct gesture. This remedial program was developed to improve pupil at-risk of dysgraphia to hold a pencil correctly and train their fine motor skills which was a pre-requirement to learn writing. This research was based on Vygotsky’s constructivist theory to produce a new remedial program. Data were collected from a preschool teacher and a preschooler in one of the Malaysia public schools through lesson observations. Moreover, document analysis on reflective journals and daily lesson plans were conducted in order to achieve a whole picture of this remedial program. The findings indicated that this remedial program was practical to scaffolding pupil who was at-risk of dysgraphia in particular to hold a pencil correctly. At the end of the study, the pupil was able to hold a pencil with the correct gesture and to start writing.